Diffuser augmented wind turbines: Review and assessment of theoretical models. (15th December 2020) - Bontempo, R.; Manna, M.
Abstract: Due to their potential to beat the Betz–Joukowsky limit for power extraction, diffuser-augmented wind-turbines have experienced a great research interest, especially in the last two decades. This paper presents a thorough critical-analysis and review of the most important theoretical models conceived for the performance analysis and design of this wind-concentrator system. The models are classified and compared between each other, and their main analogies and differences are highlighted and explained. New bridging relations between several models are also laid down. All methods are verified and validated using new and/or existing numerical and experimental data. For the first time, the impact of the simplifying assumptions, typically used in these models, is evaluated and discussed on a quantitative basis. Attention is also paid to the optimization procedures aimed at evaluating the maximum power-coefficient attainable by a diffuser-augmented wind-turbine. It is revealed that none of these procedures is valid for a given duct geometry, whereas they still offer some usefulness from a design point of view. Finally, the review points out the main limitations, shortcomings and open-issues associated with theoretical models, paving the way for future research lines and improvements of this kind of models. Highlights: The models are classified. Main analogies and differences are highlighted. New bridging relations between several models are laid down All models are verified and validated. The impact of the 1D and no-tip-gap assumptions is quantitatively evaluated. It is revealed that none of the proposed optimization procedures is general.